Reflective Practice and Teacher Professional Learning - Tuan, Do Anh (VNU Journal of Science: Education Research, 2016)
Abstract: This paper addresses the utilisation of reflective practice to foster teacher professional learning by critically reviewing recent research and other relevant literature. The paper concludes that reflection and reflective practice are vital to teacher professional learning owing to the theory-practice gap, the research-practice gap, limitations of the managerialist approach to professional development, and the unstable nature of the teaching career. Appropriate models and frameworks for reflection are available for application, accompanied by the suggestions to extend reflective practice beyond its private mode. Keywords: Reflection, reflective practice (RP), professional learning.